"Lost births, " service delivery, and human resources to health: Bringing maternal primary health care back to Canada's North. Issue 1 (5th March 2018) - Cardinal, Melissa Cora
Abstract : Purpose: The purpose of this paper is to advocate for improved service delivery of maternal-newborn care in northern Indigenous communities. This is done through critical examination of the loss of pregnancy and birthing knowledge and practice in these communities, from both a historical and contemporary lens. Supporting the return of traditional midwifery practices to the communities is the recommended solution. Design/methodology/approach: The paper is a general review of the available literature regarding Indigenous birthing practices, historical and contemporary Canadian maternal health service provision, and midwifery. Findings: Current maternal health care practice in these northern communities is not resolving service delivery and human resource inadequacies, highlighting the need for a community-based and midwifery-driven primary health care approach. Potential recommendations include implementing a comprehensive birthing initiative, innovative midwifery training, and promotion and support of the role of the community midwife. Originality/value: "Lost births" is a largely unrecognized issue in Canadian public health literature. The value of this paper lies in its potential to stimulate discourse and advocacy.